2009
DOI: 10.5145/kjcm.2009.12.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Characteristics of Urinary Tract Infections Caused byStaphylococcus saprophyticus

Abstract: Background: Staphylococcus saprophyticus is the second most common cause of urinary tract infections (UTIs) in young women. As little is known about the incidence of UTIs caused by this organism in Korea, we examined its frequency and clinical characteristics. Methods: We analyzed the frequency of S. saprophyticus among organisms isolated from urine specimens in Wonju Christian Hospital from July 1996 to June 2008 and reviewed clinical characteristics retrospectively. Results: Of 24,277 strains isolated from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…S. saprophyticus is the second most common uropathogen after Escherichia coli in uncomplicated UTI in females [ 4 ]. A nationwide surveillance study of uncomplicated UTI reported that S. saprophyticus (5.2%) was the second most common uropathogen in the total population, and significantly more common in premenopausal females [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. saprophyticus is the second most common uropathogen after Escherichia coli in uncomplicated UTI in females [ 4 ]. A nationwide surveillance study of uncomplicated UTI reported that S. saprophyticus (5.2%) was the second most common uropathogen in the total population, and significantly more common in premenopausal females [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study reported that the most common uropathogens were E. coli (53.3%) and S. saprophyticus (2.5%) among 4,734 females with uncomplicated UTI in multi-community centers [ 6 ]. A Korean study of 24,277 urinary specimen strains from 1996 to 2008 showed that the most common pathogen was E. coli (23.8%), followed by Enterococcus faecalis (11.0%), Enterococcus faecium (10.8%), Pseudomonas aeruginosa (9.0%), coagulase negative staphylococci (7.7%), Klebsiella pneumoniae (6.6%), Staphylococcus aureus (3.3%), S. saprophyticus (0.1%) [ 4 ]. Contrary to previous foreign studies, the isolation of S. saprophyticus was much less frequent from UTI patients in Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation